'Two Roads Diverged in [Soft]wood' Targeted Dumping, Differential Pricing Methodology, and Zeroing: US – Canada Anti-Dumping in Softwood Lumber. Issue 4 (28th October 2021) - Beaulieu, Eugene; Whittaker, Janet
Abstract: The United States and Canada have a long-standing series of disputes over softwood lumber that until now have focused on alleged subsidies and countervailing duties (CVDs). The United States changed things up this time around and the US Department of Commerce (USDOC) found dumping after applying the Differential Pricing Methodology to softwood lumber from Canada. The panel found that the USDOC erroneously aggregated export price differences when applying the differential pricing methodology (DPM), but departed from the WTO Appellate Body's previous ruling in US–Washing Machines regarding the use of zeroing and the inclusion of differential prices under Article 2.4.2 of the Anti-Dumping Agreement. To date, the United States and Canada have not been able to resolve the long-standing softwood lumber dispute, and this time the focus shifts from subsidies and countervailing duties to anti-dumping duties. It remains to be seen what happens in this specific dispute on appeal – if, and when, the WTO Appellate Body starts to function again. It will also be interesting to see whether this panel decision encourages parties to argue for, and future panels to permit departures from, Appellate Body rulings with which they disagree.